1999
DOI: 10.1017/s002531549900096x
|View full text |Cite
|
Sign up to set email alerts
|

Position and structure of the Subtropical/Azores Front region from combined Lagrangian and remote sensing (IR/altimeter/SeaWiFS) measurements

Abstract: The position and structure of the North Atlantic Subtropical Front is studied using Lagrangian flow tracks and remote sensing (AVHRR imagery: TOPEX/POSEIDON altimetry: SeaWiFS) in a broad region (∼31° to ∼36°N) of marked gradient of dynamic height (Azores Current) that extends from the Mid-Atlantic Ridge (MAR), near ∼40°W, to the Eastern Boundary (∼10°W). Drogued Argos buoy and ALACE tracks are superposed on infrared satellite images in the Subtropical Front region. Cold (cyclonic) structures, called ‘Storms’,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 22 publications
8
65
0
5
Order By: Relevance
“…Kelly & Watts, 1994;Pingree et al, 2002). The data processing methods and sla tracking techniques are given in Pingree & Sinha (1998) and Pingree et al, (1999a) and Fourier analysis of sla in time has been used to determine the periods of dominant structure at di¡erent latitudes and longitudes. ESAs ERS-1 and ERS-2 data, and CNES/NASA TOPEX/POSEIDON data for CLS 'MSLA' products were also used, even if not displayed, and for these data processing procedures the reader is referred to AVISO (1996), Le Traon et al (1995 and Le Traon et al (1998).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kelly & Watts, 1994;Pingree et al, 2002). The data processing methods and sla tracking techniques are given in Pingree & Sinha (1998) and Pingree et al, (1999a) and Fourier analysis of sla in time has been used to determine the periods of dominant structure at di¡erent latitudes and longitudes. ESAs ERS-1 and ERS-2 data, and CNES/NASA TOPEX/POSEIDON data for CLS 'MSLA' products were also used, even if not displayed, and for these data processing procedures the reader is referred to AVISO (1996), Le Traon et al (1995 and Le Traon et al (1998).…”
Section: Methodsmentioning
confidence: 99%
“…This sla was called anomaly R, R standing for Meddy (Richardson et al, 2000) or wave (Rossby) or Reference sla but it could have been T for Meddies (T0, T1, T2) and 'Taylor Wave'. R was followed in the manner of Pingree et al (1999a) which insists on continuity of structure so that some integral part of a feature is being followed. This method of tracking (as opposed to travel curves at the ¢xed latitudes presented here) allows the anomaly to change latitude and can £ag merging with other structures or splitting of structure.…”
Section: Sla Track For Rmentioning
confidence: 99%
“…1a), also a branch of the AzC, 148 becomes a prominent feature off western Iberia, the thermal subtropical front (at ~17°C) is 149 shifted northward and reaches the SW-Iberian margin [Pingree et al, 1999]. Along with this shift 150…”
mentioning
confidence: 97%
“…Overall, these results for temperature show that we can interpret maps of sla (see ¢gure 16 of Pingree et al, 1999, Can the Subtropical North Atlantic permanent thermocline be observed from space? R. Pingree et al 719 Journal of the Marine Biological Association of the United Kingdom (2002) Figure 9.…”
Section: Depth Of 108c Isotherm(m)mentioning
confidence: 75%
“…When this has been done we will then be in a better position to say what the altimeter is detecting in this region, e.g. Rossby Waves, variations in current strength, current meanders, fronts or waves and eddies (Cromwell et al, 1996;Cipollini et al, 1997;Pingree et al, 1999;Cipollini et al, 2000). Although it is shown that the altimeter data can represent the displacement of the permanent thermocline, we make it quite clear that this is an indirect result through correlation with near surface geostrophic velocity and not surface temperature.…”
Section: Introductionmentioning
confidence: 99%